1993
DOI: 10.1161/01.cir.88.5.2117
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane A2 and prostacyclin biosynthesis in children and adolescents with pulmonary vascular disease.

Abstract: BACKGROUND The pathogenesis of pulmonary vascular disease in children with congenital heart disease is incompletely understood. Thromboxane (TX) A2 and prostacyclin (PGI2) have opposing effects on platelet aggregation and pulmonary vascular smooth muscle. An imbalance in their biosynthesis could contribute to the progressive increase in pulmonary vascular resistance seen in older untreated patients with pulmonary hypertensive congenital heart disease and the thrombotic complications they may develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 35 publications
1
54
0
Order By: Relevance
“…IP receptornull mice develop more severe PAH and pulmonary arterial medial thickening in response to chronic hypoxia than wild-type mice (20). They are also more susceptible to injury-induced vascular proliferation and thrombosis and have elevated plasma levels of thromboxane A 2 (21), all common features of IPAH (22)(23)(24). In this study, we found that reduced IP receptor expression was associated with a doubling of the growth rate in IPAH compared with normal PASMCs.…”
Section: Role Of the Ip Receptor In Ipahmentioning
confidence: 60%
“…IP receptornull mice develop more severe PAH and pulmonary arterial medial thickening in response to chronic hypoxia than wild-type mice (20). They are also more susceptible to injury-induced vascular proliferation and thrombosis and have elevated plasma levels of thromboxane A 2 (21), all common features of IPAH (22)(23)(24). In this study, we found that reduced IP receptor expression was associated with a doubling of the growth rate in IPAH compared with normal PASMCs.…”
Section: Role Of the Ip Receptor In Ipahmentioning
confidence: 60%
“…'.~~ 8. 1s- 18 Vasodilator drugs seem to be useful in some patients with primary pulmonary hypertension.l*-" High closes ofcalciumchannel blockers administered to patients who respond with reductions in PAP and pulmonary vascular resistance may improve survival.2o…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PAH have increased TxA 2 (and TxB 2 ) production and decreased PGI 2 production resulting in an increased Tx:PGI 2 ratio, even with treatment. [1][2][3][4][5] Clinical trials of intravenous epoprostenol 6 and other prostacyclin analogs which are efficacious in PAH [7][8][9] were predicated on the inference that low endogenous PGI 2 (and increased Tx:PGI 2 ratio) is detrimental in PAH. Investigators have visualized circulating platelet aggregates in the blood of patients with PAH, 10 and increased platelet aggregation is associated with more severe PAH.…”
mentioning
confidence: 99%